Innovation scientific activity of medical colleges at U.S. Universities - Kulichenko, A. K.; Boichenko, M.; Куліченко, Алла Костянтинівна (Publishing House of University of Technology : Katowice, 2022)
The chapter covers the innovation scientific activity of medical colleges at U.S. Universities within engineering, design, and transfer of innovation products. Biomedical engineering deals with applying engineering principles and design concepts in the medical or biological field in the health care system for diagnostic, therapeutic, rehabilitation, and other purposes. Note that the transfer of innovative products of medical colleges at U.S. Universities is carried out within the implementation of the Bayh-Dole Act (1980) and amendments to it, adopted in the late 20th – early 21st centuries. Moreover, the problem of increasing the efficiency of transfer of products of innovation activity by developing innovation methods of assessing the commercial success of the proposed products has become relevant in current conditions.
Keywords: innovation scientific activity; medical colleges; U.S. Universities; engineering; design; transfer